Penehyclidine hydrochloride improves cognitive function of rats with brain injury via CAMP/CREB signaling pathway: Penehyclidine hydrochloride in rats with brain injury - Wang, Yuting; Zhao, Wen; Zhu, Shuhui; Wei, Liqun (Cellular and Molecular Biology, 2024)
This study explored the impact of penehyclidine hydrochloride on cognitive function in rats with brain injury. Sprague-Dawley rats (n=36) were randomly assigned to sham-operation, model, and penehyclidine hydrochloride groups. Rats in the sham-operation group underwent craniotomy, while the model and penehyclidine hydrochloride groups received brain injury models and interventions with normal saline and penehyclidine hydrochloride, respectively. Specimens were obtained two weeks post-intervention. Neurological deficits were evaluated using Zea-Longa scores, and memory was assessed with the Morris water maze test. ELISA determined brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) content. mRNA expressions of BDNF and NGF were assessed via qPCR, and phosphorylated CREB (p-CREB) protein expression was measured by Western blotting. Compared to the sham-operation group, both model and penehyclidine hydrochloride groups showed increased Zea-Longa scores. Escape latencies were longer and platform crossings were fewer in model and penehyclidine hydrochloride groups compared to the sham-operation group, but penehyclidine hydrochloride demonstrated a shorter latency and more platform crossings than the model group. BDNF and NGF content decreased in model and penehyclidine hydrochloride groups compared to the sham-operation group, with an increase in the penehyclidine hydrochloride group compared to the model group. mRNA expression levels declined in model and penehyclidine hydrochloride groups but were higher in the latter. p-CREB protein expression was lower in model and penehyclidine hydrochloride groups compared to the sham-operation group but higher in the penehyclidine hydrochloride group than the model group. Penehyclidine hydrochloride exhibited neuroprotective effects by upregulating the cAMP/CREB signaling pathway, improving cognitive function in rats with brain injury.